Implementation of Shunt Active Filter for Harmonic Compensation in a 3 Phase 3 Wire Distribution Network. (June 2017) - Shankar, V.K. Arun; Kumar, N. Senthil
Abstract: This paper explores the modeling of a Proportional Integral (PI) and fuzzy logic controller (FLC) based, shunt active power filter (SAPF) for a three wire network to compensate current harmonics fed to a nonlinear load. In the fuzzy logic controlled SAPF mathematical model of the system is not required since it is based on an inference system incorporating intelligence derived through human expertise. The PI controlled and fuzzy logic based (SAPF) have been developed using the Simulink tool box of MATLAB. Simulation results illustrate that the fuzzy logic based active filter outperforms the PI based shunt active filter. To validate the simulation results a hardware setup is developed making using of the instantaneous Id-Iq theory using for a three phase three wire system. The hardware results were found to match closely with simulation outputs.